Evanescent wave optical trapping and transport of polystyrene microspheres on microfibers. Issue 11 (27th August 2014) - Irawati, N.; John, V.; Aeinehvand, M. M.; Ibrahim, F.; Ahmad, H.; Harun, S. W.
ABSTRACT We investigate the manipulation of polystyrene microspheres using the evanescent optical field surrounding a silica microfiber. The microfiber is produced using a flame brushing technique from a standard single‐mode optical fiber. It is observed that the polystyrene microspheres can be attracted and trapped along the microfiber by means of evanescent field, which provides both scattering and gradient forces. The number of microspheres attached to a microfiber decreases in a quadratic manner with the increase in microfiber waist diameter. Scattering and gradient forces exerted on the microspheres also depend on the microsphere size where a larger number of polystyrene microspheres were seen attached to the microfiber if the microsphere size is smaller. It is also observed that the microspheres attached to the microfiber are propelled along the microfiber in the direction of the propagating light. These results show that the proposed optical trapping mechanism can be used for manipulating and identifying minute biological objects such as bacteria, yeast, and organelles. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2630–2634, 2014